Wordwall and Interactive Flat Panel (IFP) as Student-Centered, Deep Learning-Based Media for Islamic Education in Elementary Schools - Reineta Kusumawati; Azka Mushoffa; Azkia Tsany Baharsyah (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2026)
Low student participation and motivation in Islamic Religious Education (IRE) learning at the elementary school level remain pressing pedagogical challenges in the digital era. This study offers a distinctive contribution through the integration of two technological platforms simultaneously Wordwall as a gamification-based learning medium and the Interactive Flat Panel (IFP) as a touch-based interactive display within a structured and student-centered IRE learning ecosystem. Unlike previous studies that have examined educational technologies separately, this research explores the synergy between these two platforms in fostering deep learning, understood in a pedagogical context as students’ ability to analyze, reflect upon, and meaningfully internalize concepts rather than merely memorize them. The study was conducted at SDN 1 Bulusulur, Wonogiri, Central Java, Indonesia. A qualitative descriptive approach was employed through structured observations, in-depth interviews, and documentation studies. Data were analyzed using the Miles and Huberman interactive model. The findings reveal three significant outcomes: (1) students’ active engagement increased substantially, as evidenced by higher frequencies of responses and interactions during the learning process; (2) students’ understanding of Islamic values developed from a memorization-based level to the contextual application of concepts in their daily lives; and (3) the learning environment shifted from a one-way transmission model to a collaborative and reflective model centered on students’ learning experiences. These findings demonstrate that the synergy between Wordwall and the Interactive Flat Panel effectively bridges the gap between digital technology and the deep internalization of spiritual values in Islamic Religious Education at the elementary school level.